2014
DOI: 10.1002/chem.201303057
|View full text |Cite
|
Sign up to set email alerts
|

Novel Catalyst System for Hydrostannation of Alkynes

Abstract: A catalyst system was developed for the highly regio- and stereoselective hydrostannation of a range of alkynes with tributylstannane under mild conditions. The active catalytic species was generated from a stable diruthenium complex by illuminating household fluorescent light (30 W) at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 62 publications
(30 reference statements)
2
14
0
Order By: Relevance
“…This observation illustrates that the electronic properties of the alkyne substrate can alter the regioselectivity governed by the inherent topological features of the catalyst system. It is also important to note that sterically biased propargyl alcohols can be converted into b-(E)-vinylstannanes with high regioselectivity (entries [14][15][16], as has been reported previously for other hydrostannation catalysts. [4] Accordingly, the scope of the regioselective alkyne hydrostannation to (E)b-vinylstannanes using complex 1 is expanded, rather than compromised, relative to other catalyst systems.T othis end, it is noteworthy that 1 produces the (E)-b-vinylstannane isomer of mifepristone (Scheme 2) with 2:98 a/(E)-b regioselectivity and in 98 %yield, thereby demonstrating that afair degree of molecular complexity can be accommodated by the system Scheme 2.…”
supporting
confidence: 56%
See 3 more Smart Citations
“…This observation illustrates that the electronic properties of the alkyne substrate can alter the regioselectivity governed by the inherent topological features of the catalyst system. It is also important to note that sterically biased propargyl alcohols can be converted into b-(E)-vinylstannanes with high regioselectivity (entries [14][15][16], as has been reported previously for other hydrostannation catalysts. [4] Accordingly, the scope of the regioselective alkyne hydrostannation to (E)b-vinylstannanes using complex 1 is expanded, rather than compromised, relative to other catalyst systems.T othis end, it is noteworthy that 1 produces the (E)-b-vinylstannane isomer of mifepristone (Scheme 2) with 2:98 a/(E)-b regioselectivity and in 98 %yield, thereby demonstrating that afair degree of molecular complexity can be accommodated by the system Scheme 2.…”
supporting
confidence: 56%
“…It is also important to note that sterically biased propargyl alcohols can be converted into b-(E)-vinylstannanes with high regioselectivity (entries [14][15][16], as has been reported previously for other hydrostannation catalysts. Of these latter examples,the conversion of 2-hexyne into the corresponding (E)-bvinylstannane with 9:91 a/(E)-b regioselectivity is particularly noteworthy (entry 12), as this result indicates that the molecular topology accessible from 1 can finely discriminate between methyl and propyl groups on opposing ends of an unsymmetrically substituted dialkyl alkyne.H owever,w hen electron-withdrawing substituents were present, as in the case of 4-cyano-1-butyne (entry 13), the regioselectivity of the hydrostannation process was again diminished.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast to all other transition-metal-catalyzed hydrostannation reactions documented in the literature, it was recently reported that ruthenium complexes 16-18 [29][30][31] (Scheme 9) provide unique antiselectivity across various types of internal alkyne substrates to afford (Z)-alkenylstannane product (Scheme 10). A mechanistic hypothesis explaining this unique transhydrostannation of symmetrical and unsymmetrical internal alkynes in the presence of a transition metal has been reported by Fürstner (Scheme 11).…”
Section: The Particularity Of [Cp*ru]-based Complexes In the Hydrostamentioning
confidence: 99%